Polychlorinated biphenyls are associated with reduced testes weights in harbour porpoises (Phocoena phocoena). (May 2021) - Williams, Rosie S.; Curnick, David J.; Brownlow, Andrew; Barber, Jonathan L.; Barnett, James; Davison, Nicholas J.; Deaville, Robert; ten Doeschate, Mariel; Perkins, Matthew; Jepson, Paul D.; Jobling, Susan
Highlights: PCB blubber concentrations and testes weights were measured in harbour porpoises. Testes weights were negatively associated with PCB concentrations & body condition. Reproduction impact assessments of PCBs in cetaceans only focus on female impacts. Impacts of male fertility should be included in population health assessments. Abstract: Polychlorinated biphenyls (PCBs) are highly toxic and persistent aquatic pollutants that are known to bioaccumulate in a variety of marine mammals. They have been associated with reduced recruitment rates and population declines in multiple species. Evidence to date documents effects of PCB exposures on female reproduction, but few studies have investigated whether PCB exposure impacts male fertility. Using blubber tissue samples of 99 adult and 168 juvenile UK-stranded harbour porpoises ( Phocoena phocoena ) collected between 1991 and 2017, here we show that PCBs exposures are associated with reduced testes weights in adults with good body condition. In animals with poor body condition, however, the impact of PCBs on testes weights was reduced, conceivably due to testes weights being limited by nutritional stress. This is the first study to investigate the relationship between PCB contaminant burden and testes weights in cetaceans and represents a substantial advance in our understanding of the relationship between PCB exposures and male reproductive biology in cetaceans. As testes weight is a strong indicator of male fertility in seasonally breeding mammals, we suggest the inclusion of such effects in population level impact assessments involving PCB exposures. Given the re-emergent PCB threat our findings are globally significant, with potentially serious implications for long-lived mammals. We show that more effective PCB controls could have a substantial impact on the reproductive health of coastal cetacean species and that management actions may need to be escalated to ensure adequate protection of the most vulnerable cetacean populations.